Pengembangan Game Gamelan Gender Wayang Berbasis Virtual Reality - Gede Yogi Wiryawan; Dewa Gede Hendra Divayana; Gede Aditra Pradnyana (Ikatan Ahli Informatika Indonesia (IAII), 2019)
Gamelan is one of the most popular musical instruments and is admired by international gamelan residents, divided into three types, namely Javanese Gamelan, Balinese Gamelan and Sundanese Gamelan. One of the Balinese Gamelan instruments that is still used today is Gender Gamelan. Gamelan Gender Wayang has almost the same function as gamelan music in general, but the Gamelan Gender Wayang is not accompanied by other musical attributes such as dots or flutes. The purpose of this study is to develop Gamelan Gender Wayang Games Based on Virtual Reality so that this application can facilitate the younger generation in learning the Gamelan Gender Wayang music. This application allows users to feel the atmosphere of playing gamelan in general with the help of an HTC VIVE tool. This Virtual Reality Based Gamelan Gender Wayang Game Development uses the ADDIE model. There are five stages in the ADDIE model, namely Analysis (Analyze), Design (Design), Development (Development), Implementation (Implementation), and Evaluation (Evaluation). Product development with this model can produce good products, because at each phase that is passed can evaluate. Tests to find out the response of the community after using the Gamelan Gender Wayang Game Based on Virtual Reality were conducted using the questionnaire method and had results with an average percentage of 87.72% which means the application was in a very good category.